Associations between sleep habits, performance in reading and mathematics, and inattention and hyperactivity, - Katrina L. Grasby; Sally A. Larsen; Alice M. Gregory; Sarah Blunden; Katie S. Lewis; Juan J. Madrid-Valero; William L. Coventry; Brian Byrne; Richard K. Olson (PLoS ONE, 2026)
This study examined relations between sleep, reading and mathematics, and inattention/hyperactivity in childhood and adolescence in a sample of Australian twins (maximum n = 5524; 51% female; 95% European ancestry; M age 8.6–14.6 years). Between and within models were used to assess if (a) differences between twins, or (b) differences between families, in five facets of sleep habits were associated with academic and behavioral measures. Some sleep measures uniquely predicted reading and mathematics in some grades, but overall, sleep quality, duration, bedtime regularity, daytime sleepiness, and snoring accounted for only ~1% of the academic variance. However, sleep measures accounted for up to 7% of the variance in inattention/hyperactivity. Post hoc analyses showed that inattention mediated most of the associations between sleep and reading and mathematics outcomes that were detected. This study adds to the literature showing small and inconsistent relations between sleep and academic performance in normative samples of children and adolescents.